Factors Affecting Farmer’s Exchange Rate of Sugar Cane Farmer Plasma in PTPN XI - Muhammad Zul Mazwan; Masyhuri Masyhuri (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
This study aimed to determine the exchange rate and its affecting factors of plasma cane farmers in PTPN XI. This research involved 95 farming land cane farmers and 95 moor land cane farmers. The concept on this research are the concept of subsistence and multiple linear regression analysis method. The result showed, the exchange rate of plasma cane farmers of PTPN XI is 90.87% while that of moor land plasma cane farmers is 90.01%. This means that the average welfare status of cane farmers can be said to be not prosperous. Factors increasing the plasma cane farmers’ exchange rate on farming land are cane farm productivity, land area and rendement of cane, while on dry land are land area and the yield of sugarcane. On the other hand, factors descreasing the plasma cane farmers’ exchange rate on farming land are farmer’s experience, price of seed, price of inorganic fertilizer and price of labor, while on dry land are number of family members and cost of labor. The government needs to raise the Highest Retail Price of sugar. Government programs to support the production facility incentive in sugarcane farming activities are required, intended to decrease the production cost of sugarcane and provide motivation to improve the FER of plasma sugarcane. Agricultural intensification efforts are conducted by adding the inputs that are able to increase the FER.